2000
DOI: 10.1038/sj.bmt.1702234
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and pulmonary toxicity in patients undergoing high-dose chemotherapy for lymphoma and breast cancer: prognostic factors

Abstract: Summary:We sought to define risk factors predisposing breast cancer and lymphoma patients to cardiac and pulmonary toxicity when undergoing high-dose chemotherapy (HDC) and autologous stem cell rescue (ASCR). Additionally, we evaluated in depth the predictive value of the ejection fraction measured prior to HDC in determining cardiac toxicity. In this retrospective analysis, 24 variables were examined in 138 patients undergoing HDC and ASCR from 1990 until 1995. Logistic regression models were used to model th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 40 publications
1
56
0
2
Order By: Relevance
“…In at least seven studies, LVEF measured at rest was unable to predict future cardiac toxicity. 17,28,79,80,100,104,105 One of these studies also showed that measurement of cardiac reserve during exercise could not predict cardiac morbidity or mortality. 104 On the other hand, three studies reported a significant association between pre-transplant LVEF and cardiotoxicity 18,54,77 and two more described a trend in the same direction.…”
Section: Predictive Value Of Pre-hd Chemotherapy Cardiologic Evaluatimentioning
confidence: 99%
See 2 more Smart Citations
“…In at least seven studies, LVEF measured at rest was unable to predict future cardiac toxicity. 17,28,79,80,100,104,105 One of these studies also showed that measurement of cardiac reserve during exercise could not predict cardiac morbidity or mortality. 104 On the other hand, three studies reported a significant association between pre-transplant LVEF and cardiotoxicity 18,54,77 and two more described a trend in the same direction.…”
Section: Predictive Value Of Pre-hd Chemotherapy Cardiologic Evaluatimentioning
confidence: 99%
“…Other authors found a trend towards significance also. 78,80 Besides the inconsistent data in the literature, the potential contribution of previous anthracycline exposure to HD chemotherapy-associated cardiac toxicity should be reconsidered based upon recent insights about the progressive establishment of cardiac damage by anthracyclines. The long known assumption that the incidence of chronic cardiomyopathy is minimized by restricting the cumulative doxorubicin dose less than 400 mg/m 281 has been recently challenged.…”
Section: Previous Anthracycline Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-one patients have undergone NMSCT following conditioning with melphalan and fludarabine at our institution for multiple myeloma (11), chronic lymphocytic leukaemia (3), chronic myeloid leukaemia (2), acute lymphoblastic leukaemia (2), non-Hodgkin lymphoma (1), acute myeloblastic leukaemia (1), and paroxysmal nocturnal haemoglobinaemia (1). All received a total fludarabine dose of 150 mg/m 2 over 5 days (day −6 to day −2 inclusive) in addition to melphalan 120 mg/m 2 (four cases) or 140 mg/m 2 (17 cases) on day −1.…”
Section: Case Reportsmentioning
confidence: 99%
“…Radiation therapy to the chest wall may cause direct cardiac toxicity or augment the effects of chemotherapy. Some reports indicated that prior radiation therapy to the mediastinum or chest wall is an independent predictor of cardiotoxicity in patients with lymphoma and breast cancer undergoing high-dose chemotherapy (6,7).…”
mentioning
confidence: 99%